Behavioral Economic Theory: a Methodological Breakthrough or Extension of the Boundaries of Dominant Orthodoxy? - O. Nesterenko; M. Zdvizova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article is devoted to the analysis of the place of behavioral approach in the structure of modern economic study. The evolution of views on the essence of economic behavior of individuals is described and the peculiarities of approaches to its definition of different economic schools are analyzed. The comparative analysis of behavioral and neoclassical approaches is presented; the peculiarity of the used method is the presentation of the neoclassical direction not in the aggregate, but as two main branches – cardinal and ordinal, which allowed for a more detailed analysis. The analysis revealed differences and some similarity of these directions of research. According to the findings, it is concluded that the behavioral approach is not the complete opposite of the neoclassical, but has a significant number of features close to the ideas of ordinary people, so it can be considered as a natural continuation of established ideas deepened through the use of an interdisciplinary approach. The article also outlines possible options for the development of neoclassical and behavioral approaches and the current issues for further research.